Characterization of size segregated PM10 at a rural site in the Eastern Mediterranean - Genç Tokgöz, D. Deniz (Environmental Research and Technology, 2025)
Size-resolved PM10 samples (PM10-2.5 and PM2.5) were collected at a rural site located in the northeastern Mediterranean between August 2010 and April 2013. A total of 461 PM10 aerosol samples (461 PM2.5 and 461 PM10-2.5) were analysed for major and trace elements (Na, Mg, Al, Si, S, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Zn, As, Ba and Pb) and anions (Cl-, NO3- and SO42-). Crustal elements and sea salt particles were found to be mainly associated with the coarse fraction (>60%), whereas SO42- and NO3- were predominantly found in the fine mode (>80%). The crustal originated species exhibited very strong correlations (r>0.9) in the coarse fraction and PM10, while their correlations were slightly lower in the fine fraction (0.5< r < 0.8). Concentrations of most aerosol species exhibited well-defined seasonal variation with higher concentrations in summer than winter. The difference between summer and winter concentrations were not significant for As, Ca, Cr, Pb and NO3-. During the sampling period, 11 specific Saharan dust events were identified.